Molecular profiling of BRCA1/BRCA2 gene variants in Pakistani breast cancer patients - Ghulam, Bushra; Muhammad Afzal; Amena Rahim; Zahira Bashir; Naila Zakria; Ahmad Abubakr (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the frequency of genetic variants in breast cancer types 1 and 2 gene in breast cancer Pakistani patients. Method: The case-control study was conducted at the Islamic International Medical College and Pakistan Railway Hospital, Rawalpindi, Pakistan, from October 2022 to August 2023, and comprised females with breast cancer in group A, with an age range of 23–83 years (mean 51.9 years with SD ± 10.8 years) and as many healthy, age-matched female controls in group B, with age range of 26–82 years (mean 57.8 years with SD ±10.1 years). Peripheral blood samples were taken from all the participants. Allele-specific tetra amplification refractory mutation system-polymerase chain reaction was used to determine the frequency of c.4485G>A, c.4508C>A, c.5278G>C and c.5503C>T genetic variants in breast cancer type 1 gene, and c.92G>A and c.3109C>T genetic variants in breast cancer type 2 gene. Data was analysed using SPSS 27. Results: Of the 336 female participants 168(50%) were in each of the 2 groups. None of the group B controls had genetic variants in breast cancer type 1 and 2 genes. In group A patients, 4(2.3%) had the variant c.4485G>A in breast cancer type 1 gene, while other breast cancer type 1 variants were negative. Also, 9(5.3%) group A patients had variants c.92G>A and c.3109C>T in breast cancer type 2 gene. Conclusion: Cost-effective, polymerase chain reaction-based genetic testing could effectively identify mutant variants of breast cancer types 1 and 2 genes in the Pakistani population. Key Words: Breast cancer, BRCA1, BRCA2 genes, Allele-specific ARMS-PCR, Genetic testing.